Participatory Community Based Islamic Boarding School Da'wah Management Strategy to Strengthen Local Islamic Da'wah in Lumajang - Safitri, Anis; Subahri, Bambang (IJoIS: Indonesian Journal of Islamic Studies, 2025)
This study analyzes the pesantren-based da'wah management strategy at the Miftahul Ulum Islamic Boarding School in Banyuputih Kidul Lumajang, emphasizing the integration of a participatory approach in da'wah management practices. The study uses a descriptive qualitative approach through observation, in-depth interviews, and documentation. The findings show that pesantren da'wah management is carried out through four main functions, namely planning, organizing, implementing, and supervising. Da'wah planning is carried out in a participatory and contextual manner by involving caregivers, ustaz, administrators, and santri, so that the da'wah program is responsive to the internal needs of the pesantren and the surrounding community. Organization is collective and flexible, da'wah implementation is carried out through internal and external da'wah with a persuasive-educational approach, while supervision is carried out continuously even though it has not been formalized administratively. The novelty of this research lies in the formulation of a community-based da'wah management model for Islamic boarding schools that expands the function of da'wah from internal guidance to strengthening social da'wah in the community. Theoretically, these findings enrich the study of da'wah management with a participatory perspective based on Islamic boarding schools, while practically providing an adaptive and applicable model for managing da'wah in Islamic boarding schools as centers for community religious empowerment.